PERAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM AKUNTABILITAS PENGELOLAAN DANA DESA TAHUN 2020 DI DESA KALIGAWE WETAN KECAMATAN SUSUKANLEBAK KABUPATEN CIREBON - Mochammad Reza Rewaldhi; Husen Saeful Anwar; Ibnu Malik (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
This study dissects how the administration of the Village Fund Allocation is done by the Kaligawe Wetan Village Government and the job of the BPD in acknowledging ADD Accountability. The examination technique utilized by the scientist is distinct strategy. The outcomes showed that the job of the BPD in the ADD arranging stage in Kaligawe Wetan Village was to convey the goals of the local area in the Musrembangdes and the job of the BPD in settling on choices at the improvement arranging stage which will be understood and afterward the choice is gone ahead in a town guideline that has been concurred with the town government. In the execution of the Village Fund Allocation, the BPD likewise goes about as an administrative organization for exercises, while at the ADD responsibility stage, the BPD has the commitment to appoint that the execution of ADD should run by the material guidelines.